DESAIN ALAT ANGKAT UNTUK PEMASANGAN CETAKAN DI MESIN INJEKSI PLASTIK ARBURG 420 C - Amanda Renata; Muhammad Fajri Adzan; M Yunus; Shanty Dwi Krishnaningsih (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
In this final project, a lifting device was designed for the installation of molds on the Arburg 420 C plastic injection machine due to the problems with the large dimensions of the molds that could not be installed on the machine. Therefore the purpose of this final project is to create a lifting equipment degin for the installation of a 500mm X 400mm dimension mold that can lift the mold with a maximum weight of 700kg. in this final project, Auto CAD software is used to draw 2D designs and Solidworks to analyze the stress analysis. The method used is VDI 2222 methode. This method is carried out in 4 stages: plan, concept, design, and finish. The result of this final project is a lifting equipment is able to lift the molds with a maximum weight of 700kg. techically the frame of this tool is able to lift the molds with a maximum load of 1 tonne.